2017
DOI: 10.1590/1982-7849rac2017160037
|View full text |Cite
|
Sign up to set email alerts
|

A Escolha de Fundos de Ações e o Investidor Individual

Abstract: Resumo Este artigo propõe um modelo de pontuação para a escolha de fundos de investimento em ações (FIAs) brasileiros de gestão ativa com alfa de Jensen positivo e significativo. Duas medidas de desempenho e oito características dos FIAs foram obtidas entre 2004 e 2014. O conjunto de características é amplo e foi codificado como variáveis binárias. A amostra conta com 1.417 fundos e minimiza o viés de sobrevivência porque inclui FIAs iniciados e encerrados. A pontuação foi estimada por regressão logística biná… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
12

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 20 publications
2
6
0
12
Order By: Relevance
“…Thus, the empirical evidence indicates that larger and younger funds are capable of delivering higher performance measured by the alpha. These results support the studies by Mendonça et al (2017), who argue that more recent funds tend to achieve better performance, and are in line with the empirical evidence of the studies by Castro and Minardi (2009) and Milani and Ceretta (2013), who found positive relationships between fund size and performance.…”
Section: Turnover Versus Performance Relationshipsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, the empirical evidence indicates that larger and younger funds are capable of delivering higher performance measured by the alpha. These results support the studies by Mendonça et al (2017), who argue that more recent funds tend to achieve better performance, and are in line with the empirical evidence of the studies by Castro and Minardi (2009) and Milani and Ceretta (2013), who found positive relationships between fund size and performance.…”
Section: Turnover Versus Performance Relationshipsupporting
confidence: 91%
“…As Milani and Ceretta (2013) note, larger funds may benefit from economies of scale, which could explain the positive relationship between size and performance. Finally, it was found that younger funds achieve better performance, as argued by other authors (Ferreira et al, 2013;Mendonça et al, 2017;Silva et al, 2018).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…A idade se mostrou significante em duas formas de mensurar o desempenho com sinais opostos, sendo negativo (Berggrun et al,2014;Mendonça et al, 2017;Silva et al, 111 2018) para o Alfa de Jensen e positivo (Milani & Ceretta, 2013;Alda, Andreu, & Sarto, 2017) para o retorno anual, podendo indicar que, em alguns casos, a idade do FIA representa sua sobrevivência no mercado e o prestígio do ponto de vista de seus investidores (Golec, 1996). (Bertin & Prather;2009;Golec, 1996).…”
Section: Corrupunclassified
“…Idade do Fundo (AGE) -Logaritmo natural da idade do Fundo no início de cada ano da amostra. Considerando que estudos anteriores apontam tanto relação positiva (Golec, 1996;Milani & Ceretta, 2013;Alda, Andreu, & Sarto, 2017) quanto negativa para essa variável (Berggrun, Mongrut, Umana, & Varga, 2014;Mendonça, Campani, & Leal, 2017;Silva et al, 2018), o sinal esperado é indefinido.…”
unclassified